(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Oral cavity hygiene has gained significance in recent years. Dental plaque is the community of microorganisms found on tooth surface as bio-film embedded in matrix of polymers of host and bacterial origin.Dental plaque is considered to be main causative factor for both dental caries as well periodontal disease. Although mechanical oral hygiene at home remains single most reliable means of cleaning teeth, however majority of people do not carry out regular activities like brushing daily due to unawareness of correct brushing techniques as well as duration hence use of mouth rinses has been widely advocated as an adjunctive treatment.Variety of antimicrobial mouthwashes are being used to treat plaque causing microorganisms however many times these mouthwashes are known give rise to adverse oral manifestations such as altered taste sensations soreness of oral mucosa/ tongue discoloration as well as staining.Herbal extracts have been used in traditional medicine for several thousand years as they are cheap and have little side effects.Herbal Medicine is still mainstay of about 75 to 80% world population mainly in developing countries for primary health care because of general belief that herbal drugs are without side effects besides cheap and locally available. According to World Health Organization, the use of herbal remedies throughout world exceeds that of the conventional drugs by two to three times.This article aims at brief description of common herbs such as Curcuma Longa, Acacia Arabica, Azadirachta indica Cymbopogon Citratus, Ocimum Sanctum, Salvadora Persica, Acacia Catechu, Aloe Barbadensis, Juglans Regia, Guaijaverin and their use. Herbs may appear to potential alternative to current treatment modalities however more research is required.